2003
DOI: 10.1597/1545-1569(2003)040<0225:dotgfa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Transforming Growth Factor-β2-Perturbing Antibody in a Collagen Vehicle Inhibits Cranial Suture Fusion in Calvarial Organ Culture

Abstract: These results support previous reports suggesting a role for Tgf-beta2 in cranial suture fusion. In cell culture the collagen gel, both with and without anti-Tgf-beta2 antibody, promoted similar osteoblast attachment, proliferation, and osteoblastic morphology. In organ culture anti-Tgf-beta2 antibody was delivered in a bioactive state via a collagen gel to inhibit cranial suture fusion. Also, the results suggest that the inductive effect of fibroblast growth factor-2 is not dependent on Tgf-beta2 activity. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Although most CG have reportedly been able to enhance osteogenesis, [36][37][38] it is important to note that this particular gel exhibited an inherent inhibitory effect on cell proliferation, matrix production, and bone mineralization 39 and thus was proposed to prevent bone formation along cranial suture sites. 40 Contrary to these reports, however, we observed robust mineralization with the largest amount of ectopic bone in mice treated with these gels after being loaded with MDSC-B4.…”
Section: Usas Et Almentioning
confidence: 99%
“…Although most CG have reportedly been able to enhance osteogenesis, [36][37][38] it is important to note that this particular gel exhibited an inherent inhibitory effect on cell proliferation, matrix production, and bone mineralization 39 and thus was proposed to prevent bone formation along cranial suture sites. 40 Contrary to these reports, however, we observed robust mineralization with the largest amount of ectopic bone in mice treated with these gels after being loaded with MDSC-B4.…”
Section: Usas Et Almentioning
confidence: 99%
“…Erk1/2 activity is a critical regulator of Fgf2 signaling during suture closure, as blocking Erk1/2-P abrogated the effect of Fgf2 on suture closure (Kim et al, 2003). Tgf-␤2 also induced premature suture closure both in vitro and in vivo (Opperman et al, 2000;Moursi et al, 2003); Mooney et al, manuscript submitted for publication). The present study showed that Erk1/2-P was also required for Tgf-␤2 regulation of suture patency, suggesting that signaling by means of Erk1/2 is required for the induction of suture closure.…”
Section: Discussionmentioning
confidence: 99%
“…Fgf2 treatment has been shown to induce premature suture closure (Kim et al, 1998(Kim et al, , 2003Ignelzi et al, 2003), and the map kinase Erk1/2 signaling pathway was required for Fgf-stimulated suture closure (Kim et al, 2003). In both in vitro and in vivo experiments, Tgf-␤3 rescued sutures from obliteration, whereas Tgf-␤2 induced suture obliteration (Opperman et al, 2000(Opperman et al, , 2002Chong et al, 2003;Moursi et al, 2003). Tgf-␤2 and Tgf-␤3 use the serine/threonine kinase Smad2/ Smad3 signaling pathway (Centrella et al, 1996;Massague and Wotton, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The synostosed rabbits from this colony share important morphological features with human infants exhibiting congenital bicoronal craniosynostosis. Phenotypically, these rabbits show bony bridging at the coronal sutures as early as 21 days gestation, obliterated coronal sutures at birth, coronal ridging, and 1 We have adopted the convention used by Moursi et al (2003) in abbreviating both the gene product and antibody against it with only the first letter capitalized: Tgf-β2. et al, 1994a, 1994b, 1998b, 2002).…”
Section: Samplementioning
confidence: 99%
“…Although the pathogenesis of simple, nonsyndromic craniosynostosis is not well understood, Loeys et al (2005) show that mutations in TGF-β receptor 1 and 2 are associated with some cases of craniosynostosis in humans, and experimental manipulations of Tgf-β isoforms in various studies (Mehrara et al, 2002;Chong et al, 2003) corroborate their importance in maintenance of cranial suture patency and fusion. Specifically, inhibition of Tgf-β2 using neutralizing antibodies in rat calvariae has successfully rescued normally fusing sutures from obliteration in vitro (Opperman et al, 1999;Moursi et al, 2003).Building upon this previous work, we explored how treatment to inhibit Tgf-β2 at the suturectomy site affects growth of the neurocranium in a rabbit model in vivo. Using the same rabbit colony, Mooney et al (2007a) demonstrated that anti-Tgf-β2 treatment delays postoperative resynostosis of the coronal suture.…”
mentioning
confidence: 99%